The Effect of Fermentation Length and Dosage of Liquid of Organic Fertilizer Banana Peel on the Growth of Red Spinach (Amaranthus Tricolor L.) - Nurul Fadhilah; Prapti Sedijani; I Gde Mertha (Jurnal Biologi Tropis, 2021)
Fertilizer substitutes elements that have been used by plants. There are two available fertilizers, inorganic and organic fertilizers. Long-term use of inorganic fertilizers on a land negatively affects the crop and the soil fertility, hence, the organic one is a better choice. This study aims to determine the effect of liquid organic fertilizer of banana peels on the growth of red spinach and determine the best treatment for red spinach growth. This study used a Completely Randomized Design consisted of 2 factors (dosage of POC banana peel and length of fermentation time). Each has 4 levels, 3 replicates. The results of data analysis using ANOVA test show that the treatment of fermentation length and dosage of POC banana peel increase growth parameters of red spinach include plant height, leaf number, leaf area, fresh weight, and dry weight, while the interaction treatment of fermentation length and dosage of POC banana peel affects almost all growth parameters, except for the leaf area parameter that shows no interaction. DMRT (ÃÂ± 5%) test shows that the best combination treatment for plant height and fresh weight is a dosage of 8 ml POC of banana peel that have been fermented for 15 days, and the best treatment for leaf number and dry weight is a dosage of 8 ml POC of banana peel that have been fermented for 10 days.